!تركيا و الحلم الأوربي: ابتعاد ام اتحاد؟ - د. طلال يونس الجليلي (PROSPECTIVE RESEARCHES, 2023)
The Joining of Turkey to the European Union is regarded to be national ambition on both the popular and formal level. But, this is countered by many obstacles, the most important one is the Turkish Islamic identity with its both historical and geographical dimensions. In this connection that the European and Christian parties are in the opposite side of the matter of joining Turkey to this Union, because it regarded to be a Christian and European center. In turn Turkeys put them selves as a pattern of living both Islam and secular in their country. So, will the Turkeys succeed in this trail and obtain the complete membership? Or the last negotiation will end all their dreams of joining the European Union.